1987
DOI: 10.1002/ajmg.1320270303
|View full text |Cite
|
Sign up to set email alerts
|

Tetrasomy 9p caused by idic (9) (pter→q13→pter)

Abstract: Cytogenetic investigation on a malformed male infant showed an extra chromosome similar to chromosome 9 in all metaphases studied. GTG, CBG, and G-11 staining suggested that the extra chromosome was an abnormal 9, permitting the identification of the chromosome constitution as 47,XY,+idic (9) (pter----q13----pter).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
2

Year Published

1990
1990
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 11 publications
1
21
0
2
Order By: Relevance
“…Recently, Eggermann et al reported on a case of tetrasomy 9p mosaicism in lymphocytes and ®broblasts, which was not prenatally detected in amniocytes [7]. The mortality rate during the 1st year of life is approximately 40% [5]. It can be assumed that most patients who survive the 1st year have mosaic constitution.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Recently, Eggermann et al reported on a case of tetrasomy 9p mosaicism in lymphocytes and ®broblasts, which was not prenatally detected in amniocytes [7]. The mortality rate during the 1st year of life is approximately 40% [5]. It can be assumed that most patients who survive the 1st year have mosaic constitution.…”
Section: Discussionmentioning
confidence: 95%
“…A total of 150 ng labelled test-and reference-DNA, 12.5 lg unlabelled Cot1-DNA (Gibco/BRL) and 10 lg salmon sperm DNA were ethanol-precipitated and resolved in 14 ll 50% deionised formamid/10% dextransulfat in 2´SSC. Hybridisation and posthybridisation washes were performed as previously [6,7,9,14,18,20,23] b [3,5,8,10,11,17,21,22,26] c [1,2,4,19,25,28] described [13]. The metaphase spreads were harvested from male lymphocytes.…”
Section: Cgh Analysismentioning
confidence: 99%
“…Five cases [Abe et al, 1977;Wisniewski et al, 1978;Calvieri et al, 1988;Nakamura et al, 1990;Andou et al, 1994] reported that the isochromosome included a larger portion of the long arm of chromosome 9, extending to 9q21 or 9q22. While some authors [Moedjono et al, 1980;Balestrazzi et al, 1983;Shapiro et al, 1985;Grass et al, 1993] postulated that the nature of the isochromosome may influence phenotype, others [Cavalcanti et al, 1987;Schaefer et al, 1991;Andou et al, 1994;Stumm et al, 1999] found no correlation.…”
Section: Discussionmentioning
confidence: 95%
“…There have been 12 cases [Rutten et al, 1974;Orye et al, 1975;Moedjono et al, 1980;Cuoco et al, 1982;Garcia-Cruz et al, 1982;McDowall et al, 1989;Schaefer et al, 1991;Van Hove et al, 1994;Leichtman et al, 1996;Dutley et al (2 cases), 1998;Eggermann et al, 1998] reported in which the isochromosome has breakpoint at p10, with no portion of the long arm of chromosome 9 present. In nine cases [Balestrazzi et al, 1983;Cavalcanti et al, 1987;Papenhausen et al, 1990;Melaragno et al, 1992;Grass et al, 1993;Park et al, 1995;Tonk, 1997;Dutley et al, 1998;Stumm et al, 1999], the isochromosome included a small amount of the heterochromatic region of 9q, extending to 9q12 or 9q13. Five cases [Abe et al, 1977;Wisniewski et al, 1978;Calvieri et al, 1988;Nakamura et al, 1990;Andou et al, 1994] reported that the isochromosome included a larger portion of the long arm of chromosome 9, extending to 9q21 or 9q22.…”
Section: Discussionmentioning
confidence: 96%
“…Frequently described major congenital anomalies in these patients are urogenital anomalies (e.g., small penis and cryptorchid testis), skeletal anomalies (e.g., joint dislocation, clubfeet, and kyphosis), cleft lip/palate, and cardiac anomalies (ASD and VSD) [Grass et al, 1993;Schinzel, 1994]. In Table I we summarized major abnormalities and facial anomalies of 10 cases of nonmosaic tetrasomy 9p caused by the presence of an isochromosome 9p (only isochromosomes consisting of 9p material or 9p with heterochromatic material of 9q) [Moedjono et al, 1980;Garcia Cruz et al, 1982;Foerster et al, 1985;Cavalcanti et al, 1987;McDowall et al, 1989;Jalal et al, 1991;Schaefer et al, 1991;Van Hove et al, 1994;Park et al, 1995;Leichtman et al, 1996] and compared them with our case. As expected, similarities exist between our patient and previously reported tetrasomy 9p patients (including psychomotor retardation, hydrocephalus, large fontanels, hypotonia, and similar facial anomalies).…”
Section: Discussionmentioning
confidence: 97%